2014
DOI: 10.1208/s12248-014-9690-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Prediction of Human Pharmacokinetics for mAbs Exhibiting Target-Mediated Disposition

Abstract: Abstract. Prediction of human pharmacokinetics (PK) can be challenging for monoclonal antibodies (mAbs) exhibiting target-mediated drug disposition (TMDD). In this study, we performed a quantitative analysis of a diverse set of six mAbs exhibiting TMDD to explore translational rules that can be utilized to predict human PK. A TMDD model with rapid-binding approximation was utilized to fit PK and PD (i.e., free and/or total target levels) data, and average absolute fold error (AAFE) was calculated for each mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…Alternatively, a more mechanistic TMDD model that incorporates target properties can be used. Previous work has shown that the TMDD approach is more reliable for human projections because it can capture differences in target properties between species and disease populations 5 , 15 , 17 . Since both the M-M and TMDD models require parameterization of the linear CL pathway, the parameters presented herein are a useful guide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, a more mechanistic TMDD model that incorporates target properties can be used. Previous work has shown that the TMDD approach is more reliable for human projections because it can capture differences in target properties between species and disease populations 5 , 15 , 17 . Since both the M-M and TMDD models require parameterization of the linear CL pathway, the parameters presented herein are a useful guide.…”
Section: Discussionmentioning
confidence: 99%
“…11-14 For mAbs that exhibit non-linear CL due to TMDD, scaling of PK is more challenging. In order to take into account the kinetics of mAb binding to its target, a mechanistic TMDD model is required, with proper exploration of species differences in target expression and binding 5 , 15-17. …”
Section: Introductionmentioning
confidence: 99%
“…Supplementing the mAb concentration data with in vivo RO measurements can further improve the estimation of the model parameters by integrating information from different sources, thereby increasing confidence in the results and related extrapolations (8). This is especially critical when the model results obtained in preclinical species are extrapolated to humans for early clinical predictions (2).…”
Section: Mathematical Description Of In Vivo Antibody-mentioning
confidence: 99%
“…To predict human PK of antibodies that undergo TMDD, species differences of target expression levels and turnover as well as antibody interaction with target need to be considered. Scale up of the target-dependent component of antibody PK has been tackled with varying degrees of success using TMDD 7 , 8 and Michaelis-Menten (MM) 9 non-linear PK models. In both cases, appropriate scale up of the parameters that describe the PK non-linearity is critical to capture the differences across species.…”
Section: Introductionmentioning
confidence: 99%